The Secret garden [videorecording (DVD)] - Holland, Agnieszka, 1948-; Maberly, Kate, 1982-; Prowse, Heydon, 1981-; Knott, Andrew; Smith, Maggie, 1934-; Burnett, Frances Hodgson, 1849-1924 (Warner Home Video, 2009)
A young orphan named Mary is sent to live at the dark and foreboding English estate of her widowed uncle. She discovers a secret garden which was abandoned after a tragic accident. With the help of her crippled cousin Colin, and Dickon the country boy, her spirit is gradually reawakened as they bring the garden back to life.